GELOMBANG KRISIS 1997-1998: RUNTUHNYA ORDE BARU DAN LAHIRNYA BABAK BARU EKONOMI INDONESIA - Cavan Nizar Chalandra; Nurul Hidayah; Adisha Khansa Aulia (Universitas Negeri Semarang, 2025)
The 1997-1998 economic crisis was a pivotal event in Indonesian history, marking the collapse of the New Order and the beginning of democratization. This study analyzes Indonesia’s pre-crisis economic conditions, the root causes of the crisis, its unfolding dynamics, multidimensional impacts, and the government’s mitigation efforts. Using a qualitative method based on literature review from academic sources, international reports, and policy documents, the research finds that the crisis stemmed not only from external shocks such as the Thai financial collapse but also from long-standing structural weaknesses within Indonesia’s economy. These vulnerabilities included heavy dependence on foreign debt, an overvalued rupiah, a fragile banking sector, and an oligarchic economic structure. The crisis caused severe economic contraction of 13.7%, increased poverty from 15% to 33%, and triggered inflation of 77.6%. Social unrest escalated, culminating in President Suharto’s resignation in May 1998. Mitigation measures included banking restructuring through IBRA/BPPN, IMF-supported reform programs, stabilization of monetary–fiscal policies, and political reforms essential for recovery. Despite the prolonged recovery process, the crisis ultimately spurred Indonesia’s transition toward a more democratic and transparent economic system.